TANGGUNG JAWAB PENGURUS PERSEKUTUAN KOMANDITER (CV) DALAM KEADAAN PAILIT: Ahmad Fauzan Muslim - admin, admin (Reformasi Hukum, 2017)
The one of capital source of Limited Partnership in operating its business is obtained from loan of banking and non banking institution with certain guarantee. If the loan cannot be returned at the fall due and have could to be billed, hence the Limited Partnership can be expressed bankrupt by decision of Commercial Justice. CV is declared bankrupt by the Commercial Court decision, which is legally responsible are complementary ally ally because this should have an obligation to settle all the debts. Allied commanditair responsible only to ally complementary to submit a number of income (article 19 paragraph (1) Commercial code). In other words, a limited partner is only responsible to communion and complementary ally responsible inside or outside the alliance. Debtors are declared bankrupt there is irresponsible to the detriment of creditors and complicate Curator. The purpose of this study’s to know the responsibility of the Guild board Commanditaire if declared bankrupt and to identify any obstacles faced by creditors if the board of the Guild Commanditaire abdicate responsibility in it. Conclusion : (a) Allied complementary (ally active) must account for the alliance came to his personal fortune, while property ally limited partnership (ally passive) inviolability, Where ally complementary greater than one, then the responsibilities involve allies complementary other responsibilities renteng up on private property. (b) The obstacles faced by creditors if the board is not responsible Commanditaire Guild.